1998
DOI: 10.1254/jjp.76.165
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Adult Rat Hepatocytes in Primary Cultures Induced by Platelet-Derived Growth Factor Is Potentiated by Phenylephrine

Abstract: We investigated whether or not proliferation of adult rat hepatocytes induced by platelet-derived growth factor (PDGF) is affected by alpha1-adrenoceptor agonists such as phenylephrine during the early and late phases of primary culture. Adult rat hepatocytes underwent significant DNA synthesis after culture with 10 ng/ml of PDGF for 2 hr at a low cell density (3.3 x 10(4) cells/cm2). Under these culture conditions, the number of nuclei increased significantly during the 3.5-hr culture period. Hepatocyte DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…In addition, the hepatocyte DNA synthesis and proliferation produced by HGF was inhibited depending on the initial plating density. Furthermore, we found that hepatocyte DNA synthesis and proliferation were potentiated by both α 1 -and β 2 -adrenergic agonists (10).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, the hepatocyte DNA synthesis and proliferation produced by HGF was inhibited depending on the initial plating density. Furthermore, we found that hepatocyte DNA synthesis and proliferation were potentiated by both α 1 -and β 2 -adrenergic agonists (10).…”
Section: Introductionmentioning
confidence: 77%
“…Using specific inhibitors of signal transducers, we pharmacologically demonstrated that receptor tyrosine kinase, phosphoinositide 3-kinase, phospholipase C, and p70 ribosomal protein S6 kinase (p70S6K) activities are essential for HGF-induced DNA synthesis and proliferation in primary cultures of adult rat hepatocytes (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of nuclei, rather than the number of cells, was counted using a modified version of a previously described procedure (20,21). Briefly, primary cultured hepatocytes were washed twice with 2 ml of Dulbecco's phosphate-buffered saline (PBS, pH 7.4).…”
Section: Nuclei Countingmentioning
confidence: 99%
“…Effects are either mediated by cAMP-dependent protein kinase (protein kinase A, PKA; Refs. 4,12,15,26,44) or are independent of PKA and involve small guanine nucleotide binding (G) proteins (46,56,67). Both positive and negative modulation has been reported, which appeared to depend on cell type, culture conditions, or the presence of other stimuli.…”
mentioning
confidence: 99%